2020
DOI: 10.1080/02670836.2019.1705040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-planar geometry on diffusion kinetics during brazing repair process

Abstract: A new finite difference numerical model is used to study the influence of non-planar (cylindrical and spherical) solid–liquid interface geometry on the kinetics of isothermal solidification during diffusion brazing or transient liquid phase repair process. Notwithstanding that limited work had been reported on non-planar systems, this study shows that non-planarity of the solid–liquid interface can have significant effects on the kinetics of solid–liquid phase transformation during the repair process, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, they present considerable limitations from the point of view of their practical application. One of the main advantages of numerical methods [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] is that they allow more realistic boundary conditions to be accepted, for which it would not be possible to obtain analytical solutions. The accuracy of these methods is generally quite high, but they require the use of computational resources as well as a certain amount of complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they present considerable limitations from the point of view of their practical application. One of the main advantages of numerical methods [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] is that they allow more realistic boundary conditions to be accepted, for which it would not be possible to obtain analytical solutions. The accuracy of these methods is generally quite high, but they require the use of computational resources as well as a certain amount of complexity.…”
Section: Introductionmentioning
confidence: 99%
“…e effect of the geometrical shape of the dispersed drug particles on the drug release profile was examined for systems with different ratios of dissolution rate/diffusion rate and ratios of solubility/total drug loading value. Finally, Ghanbar and Ojo [46] have presented a new finite difference numerical model in order to investigate the importance of cylindrical and spherical solid-liquid interface geometry on the kinetics of isothermal solidification during diffusion brazing or transient liquid phase repair process. e obtained results showed that nonplanarity of the solid-liquid interface can have significant effects on the kinetics of solid-liquid phase transformation during the repair process which is crucial to the understanding and optimization of this process in nonplanar systems.…”
mentioning
confidence: 99%